1569. Incidence, Risk Factors, and Impact of Antiviral Prophylaxis Duration on Cytomegalovirus (CMV) Disease in High-Risk Donor Seropositive/Recipient Seronegative [D+R−] Orthotopic Heart Transplant Recipients (OHTR). (26th November 2018) - Carcoana, Allison Dumitriu; Imlay, Hannah; Fisher, Cynthia; Wong, Beatrice; Rakita, Robert; Limaye, Ajit
Abstract: Background: CMV disease is a major cause of morbidity and mortality in OHTR, especially among D+R− patients. Clinical trials of longer antiviral prophylaxis have shown reduced CMV disease incidence in kidney and lung transplant recipients but have not been done in OHTR. We aimed to characterize risk factors and impact of antiviral prophylaxis duration on CMV disease in high-risk CMV D+R− OHTR. Methods: We performed a retrospective cohort study of consecutive adult first OHTR at a single US transplant center from 5 July 2005 through 30 December 2016 with at least one year of follow-up. Standard immunosuppression included ATG induction followed by maintenance with tacrolimus, mycophenolate, and prednisone. Valganciclovir (VGCV) was given for 3 months for all R+ and for 3–6 months for D+R− at clinician discretion. CMV syndrome and end-organ disease were defined using consensus definitions. Chi square and Mann–Whitney tests were used to compare categorical and continuous variables, respectively, with P < 0.05 considered significant, and logistic regression was used for multivariate analysis. Results: Key cohort ( n = 310) characteristics included: 73% male, median age 55, 98% ATG induction, 1-year survival of 92%, and median follow-up of 44 months (IQR 22–88). Proven/probable CMV disease occurred in 27/310 (9%: syndrome 22%, end-organ 78%), and more frequently in D+R− (22/83, 27%) vs. either R+: 5/180 (2.8%) or D−R−: 0/47, P < 0.01. Among D+R− recipients who survived to hospital discharge, CMV disease occurred >1 year post-OHT in 10/22 (45%), and was genotypicallyconfirmed as ganciclovir-resistant in 4/22 (18%). Duration of VGCV prophylaxis ranged from 0 to 8.9 months (median 3.6, IQR 3.3–5.6). In a multivariable model that assessed baseline and time-dependent factors, longer durations of prophylaxis (analyzed continuously or discretely) were not associated with protection against CMV disease ( P > 0.05 for all comparisons). Conclusion: CMV disease remains a major clinical problem in D+R− OHTR, and longer durations of antiviral prophylaxis do not appear to be protective. Prophylaxis duration should be studied specifically in OHTR, rather than extrapolated from other organ transplant populations. Novel strategies to prevent CMV disease in D+R− OHTR are warranted. Disclosures: A. Limaye, Merk: Consultant and Investigator, Consulting fee and Research grant; Astellas Pharma Inc.: Consultant and Investigator, Consulting fee; Helocyte Inc.: Consultant, Consulting fee.